Caracterização e distribuição espacial do desenvolvimento sustentável dos municípios do Sudoeste do Paraná - Turra, Salatiel (2014)
The purpose of this study is to analyze the sustainable development of municipalities of Southwestern Paraná. To this end, we sought to measure the Sustainable Development Index (SDI) and identify the geographic distribution and spatial dependence of the municipalities in the region with respect to SDI. The topic is shown prominent as the discussions around the theme promote inferences that provide improvements in the management and planning of efficient public policies. With the intention of accomplishing such proposal, this study was based on quantitative models, among which Dashboard of Sustainability and Exploratory Analysis of Spatial Data. For the implementation of study, were used secondary databases from official sources such as the Brazilian Institute of Geography and Statistics, and the Paraná Institute of Economic and Social Development. The results, Stand out the low Sustainable Development Index obtained by counties in southwest region of Paraná and the disparity in the geographical distribution of SDI's municipalities, well as the low spatial dependence, despite show a positive autocorrelation. Among the conclusions of this research are low dimensional values (Environmental, Economic, Social and Institutional) that comprise the SDI of each municipality, apart from the diversity of sustainable development among municipalities. This way, intervention of public policies located and proactive actions directed to the indicators of each dimension are necessary and important, mainly, those municipalities with poor sustainable development, so that they can rectify their distortion of equity in the shortest time possible.